2008
DOI: 10.1161/strokeaha.107.502658
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Thrombectomy and Thrombolysis for Severe Cerebral Sinus Thrombosis

Abstract: Background and Purpose— Most patients with cerebral sinus thrombosis (CST) recover after treatment with heparin, but a subgroup has a poor prognosis. Those patients may benefit from endovascular thrombolysis. Methods— Prospective case series. Patients with sinus thrombosis were selected for thrombolysis if they had an altered mental status, coma, straight sinus thrombosis, or large space-occupying lesions. Urokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
122
2
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 170 publications
(130 citation statements)
references
References 20 publications
5
122
2
1
Order By: Relevance
“…Therefore, LP should be reserved for suspected severe raised ICP, including with threat to vision, when other definitive neurosurgical measures might also need to be considered. If anticoagulation is contraindicated, or in cases of severe CVT not responding to anticoagulants, endovascular thrombolysis or mechanical thrombectomy might be an option, 27,28 although evidence to support this approach is currently lacking. Steroids are not recommended and are linked to a poorer prognosis in CVT, even with the presence of parenchymal lesions, unless indicated by an underlying condition, such as meningitis or malignancy.…”
Section: Management Of Cvtmentioning
confidence: 99%
“…Therefore, LP should be reserved for suspected severe raised ICP, including with threat to vision, when other definitive neurosurgical measures might also need to be considered. If anticoagulation is contraindicated, or in cases of severe CVT not responding to anticoagulants, endovascular thrombolysis or mechanical thrombectomy might be an option, 27,28 although evidence to support this approach is currently lacking. Steroids are not recommended and are linked to a poorer prognosis in CVT, even with the presence of parenchymal lesions, unless indicated by an underlying condition, such as meningitis or malignancy.…”
Section: Management Of Cvtmentioning
confidence: 99%
“…While these studies were encouraging, a subsequent prospective trial by Stam et al 67 demonstrated less positive results. These authors chose 20 patients whose disease was presumed to have a poor prognosis; 14 had hemorrhagic infarcts at the time of enrollment, and the average initial Glasgow Coma Scale score for the entire group was 7.6.…”
Section: Fibrinolytic Agentsmentioning
confidence: 95%
“…To better elucidate the role of this methodology, several trials and case studies have been conducted (Table 1), 3 of which are particularly notable. 32,67,72 Frey et al 32 treated 12 consecutive patients with combined tissue plasminogen activator and heparin. All 12 patients had significant symptoms without evidence of convalescence, and there was MR imaging evidence of hemorrhage in 7.…”
Section: Fibrinolytic Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is generally reserved for patients with poorer prognoses (Stam 2005), as there is the potential that thrombolysis may cause death or dependency in up to 40% of patients with CVT (Stam, Majoie et al 2008). However, in critically ill patients, thrombolysis may reduce death compared to other treatments or no treatment at all (Canhao, Falcao et al 2003).…”
Section: Treatmentmentioning
confidence: 99%